Letter from John Carney to the INAAVD regarding a subscription to the fund, - Carney, John Scotland (1918)
Carney requests the INAAVD send him the addresses of J. W. Russells and the Land Commissioners Office. Letter sent from "726 Gavan Rd, Gavan Glasgow.".